O013 Anxiety and depression in adults referred for diagnostic sleep studies at an Australian tertiary sleep referral centre. (9th November 2022) - Gordon, A; Pradeepan, S; Paech, G
Abstract: Background: Depression, anxiety and sleep disorders are frequently comorbid. Our study sought to understand local prevalence of depression and anxiety; and their interaction with sleep disordered breathing, sleep quality and sleepiness. Methods: Apnoea hypopnoea index (AHI), arousal index (AI) and sleep efficiency (SE) were extracted from sequential in-laboratory diagnostic sleep studies (n=996) over three years and linked to demographic data and routine patient questionnaires (Epworth Sleepiness Scale (ESS), Hospital Anxiety and Depression Scores (HADS), and comorbidities). Anxiety or depression was either self-reported, or determined by HADS A ≥11 or D ≥8. Regression modelling was used to determine the effect of anxiety and depression on ESS, AHI, SE and AI. Significance was p<0.05 and mean±SD or median(IQR) are reported. Progress/Results: Participants were: 49.3% male, BMI 34±8.9Kg/m2, and age 50±17.0 years. Sleep indices were: AHI 18.2(5.3-43.6)/h, AI 17.7(9.8-30.9)/h, and SE 77.2±13.4%. Anxiety alone, depression alone or both were present in 75 (7.5%), 177 (17.8%) and 359 (36%) patients respectively. Raised HADS anxiety/depression scores in the absence of self-reported diagnoses were present in 91 (9.1%) and 136 (13.7%) subjects. The presence of anxiety or depression did not affect AHI, but increased ESS by 2.2 (p<0.001), AI by 3.3/h (p<0.01) and reduced SE by 1.7% (p=0.05) compared to their absence. Intended outcome/Discussion: Diagnoses of depression or anxiety are associated with poorer sleep quality and increased sleepiness despite similar AHI. Screening patients for depression/anxiety is suggested given frequent raised HADS scores without a formal diagnosis, and the higher prevalence compared to the general population.